Analisis Implementasi Prudential Principle dalam Pemberian Pembiayaan Multiguna di Bank Sumsel Babel Cabang Syariah Pangkalpinang - Ratri Winari (JYRS: Jurnal Online Mahasiswa Program Studi Fakultas Syariah dan Ekonomi Islam, 2022)
Multipurpose financing is a product that is in demand by customers of Bank Sumsel Babel, Pangkalpinang Sharia Branch. Because it is in demand, it has resulted in fraud by the customer when making a financing request, namely falsifying the value on the salary slip and the customer does not recognize the customer's status. This financing product has little possibility of financing problems, due to the maximum prudential principle in providing financing. This study aims to determine the process of providing multipurpose financing at Bank Sumsel Babel, Pangkalpinang Syariah Branch and to determine the implementation of the prudential principle in multipurpose financing at Bank Sumsel Babel, Pangkalpinang Syariah Branch. This type of research is a field research with a qualitative approach. Sources of data used are primary and secondary data sources. The research informants were the Financing Analyst, Financing Estimator, Financing Jurisprudent and Financing Administration. Data collection techniques through observation, interviews and documentation. The validity of the data used is the credibility test or trust test. While the data analysis technique of this research is to use an interactive model with data collection stages, data reduction stages, data display stages and conclusion or verification stages. The results of this study indicate that first, the process of providing multipurpose financing at Bank Sumsel Babel, Pangkalpinang Sharia Branch goes through several stages, namely submitting a financing application by the customer, after which the bank calculates and negotiates with the customer for financing application, the customer fills in the form and completes the requirements, the customer submit completed requirements and forms, the contract is executed, and disbursement of customer financing. Second, the implementation of the prudential principle in multipurpose financing at Bank Sumsel Babel, Pangkalpinang Sharia Branch using analysis of the 5C principles (character, capital, capacity, collateral, constraint of economy) and 2P (purpose and protection).